2018
DOI: 10.1002/acp.3453
|View full text |Cite
|
Sign up to set email alerts
|

Is visual–perceptual or motor expertise critical for expert anticipation in sport?

Abstract: A prominent topic is whether visual or motor expertise makes greater contribution to expert visual anticipation in sport. This stems from psychological theories, such as common coding theory, which predicts perception and action can inform each other in a bidirectional manner. This paper reviews the literature that has investigated visual and motor expertise contributions to expert visual anticipation in sport. First, psychological theories are discussed that predict visual and motor contributions to perceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…These data could be considered as emanating from anticipatory responses, according to Hick´s law for choice reaction times (Hick, 1952). This high level of anticipatory performance could be underpinned by a greater accumulation of visuomotor experiences in sport (Brenton & Muller, 2018). For example, Cañal-Bruland et al (2011) found that high-skill volleyball players outperformed the outcome of opposition attacks in beach volleyball, compared to high-skill volleyball referees, because they previously had more specific visual and motor experiences in that sport.…”
Section: Discussionmentioning
confidence: 99%
“…These data could be considered as emanating from anticipatory responses, according to Hick´s law for choice reaction times (Hick, 1952). This high level of anticipatory performance could be underpinned by a greater accumulation of visuomotor experiences in sport (Brenton & Muller, 2018). For example, Cañal-Bruland et al (2011) found that high-skill volleyball players outperformed the outcome of opposition attacks in beach volleyball, compared to high-skill volleyball referees, because they previously had more specific visual and motor experiences in that sport.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that past experiences in padel helped participants to develop an effective visual pattern, driving their gaze behaviours toward the relevant locations available in the sport environment. This accumulation of previous visuomotor experiences has been useful for expert athletes’ performance [ 60 ]. Specifically, the accumulation of these bodily experiences has been useful for guiding motor responses of players because (i) the exposure or familiarity to a situation or context helps them to read those cues related to opponents’ movements and object flight to anticipate their actions ( perceptual experience hypothesis), and (ii) the capability to perform a motor skill facilitates how an athlete perceives the environment ( motor experience hypothesis) [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the pickup of visual–perceptual information by an observer maps onto their motor representation and facilitates a motor response. Thus, when an observer picks up visual cues from an opponent, this perceptual–motor representation facilitates the anticipation of the subsequent action (Brenton & Müller, 2018). In other words, experience performing a motor task (e.g., tennis serve) should enhance anticipation ability for the same task (i.e., predicting whether an opponent’s serve will be to the receiving player’s forehand or backhand side).…”
Section: Discussionmentioning
confidence: 99%